István Szikinger is 70 years old (Academic Journal of Internal Affairs, 2022)
On this significant anniversary, we greet the professor of constitutional law, the excellent habilitated teacher, the renowned lecturer in police training, one of the founders of law enforcement science, the only member of the Hungarian Law Enforcement Society who has been awarded the Lifetime Achievement Award, the conscientious lawyer and last but not least, the former editor-in-chief of Belügyi Szemle, who is for almost four decades a regular author of the journal.
Keywords: greeting; constitutional law; law enforcement science; oeuvre